Amine-containing nanogel particles supported on porous carriers for enhanced carbon dioxide capture. (1st November 2019) - Gao, Jubao; Liu, Yida; Hoshino, Yu; Inoue, Gen
Highlights: Nanogel particles for CO2 capture with lower cycles (303–348 K) are developed. Carbon paper as supporter shows higher CO2 capacity, adsorption and desorption rate. Avrami's fractional order model accurately predicts the CO2 uptake behaviors. The CO2 capture process is governed by film and intraparticle diffusion resistance. Carbon paper as supporter shows lower sensible heat and desorption activation energy. Abstract: Amine-containing nanogel particles with a lower cooling and heating cycles (303–348 K), which is beneficial to limit the degradation and volatile of amine, has been developed as promising absorbents for CO2 capture. It is extremely important to understand the CO2 capture kinetics and mechanisms for design and operation of corresponding processes. In present work, poly tetra fluoroethylene and carbon paper were used to support the GPs by filtering and loading method. The CO2 uptake and release performance of poly tetra fluoroethylene and carbon paper supported nanogel particles was measured. It was found that carbon paper as supporter shows higher CO2 capacity and desorption rate. A comparison of three different kinetic models shows that carbon paper as supporter gives a more enhanced kinetic behavior. Avrami's fractional order model presents the best fit to experimental data. To further investigate the mechanism of CO2 uptake on absorbents, interparticle diffusion model, intraparticle diffusion model and Boyd's film diffusion model were also applied. Film diffusion resistance governed the mass transfer rate of CO2 uptake on studied absorbents at the initial CO2 uptake stages. In the following stages, intra-particle diffusion resistance plays a major role until the equilibrium is reached. The sensible heat of carbon paper as supporter is about 25% lower than that of poly tetra fluoroethylene as supporter. The desorption activation energy obtained from the Arrhenius equation is 18 kJ/mol for carbon paper as supporter, which is 84% lower than that of the typical aqueous MEA solvent.